Stabilisation of Geomaterials using Microbially Induced Calcium Carbonate Precipitation - Porter, Hannah Elizabeth (Curtin University, 2018)
The Australian landscape has a large number of naturally cemented structures, which provide inspiration for a sustainable cementing material which does not produce carbon dioxide during the manufacturing phase. Structures such as corals, beach rocks and stromatolites are cemented through the process of Microbially Induced Calcium Carbonate Precipitation, (MICP). This thesis reports on the potential for MICP as a replacement or augmentation to chemical binders in geomaterials and evaluates the sustainability of MICP using Life Cycle Analysis.